Simultaneous Saccharification and Fermentation (SSF) of Blended Organic Fertilizer from Yam and Sweet Potato Peels - Abershi, Ajiduku Leyoa; Stephen, Ezeonu Chukwuma; Clinton, Umeh Chisom (Darul Yasin Al Sys, 2024)
This study shows the production of organic fertilizer by utilization of yam and sweet potatoes peels through Simultaneous Saccharification and Fermentation (SSF) Method. Samples are categorized into sun-dried, sundried and autoclaved, Heat-dried, heat-dried and autoclaved, the fermentation process is carried out using alpha amylase and saccharomyces cerevisiae. Investigation of mineral elements (N, Cd, P, Zn, Pb, As, K, Hg.), in the eight varieties of Organic Fertilizer produced shows concentration of Cadmium (Cd) ranges from 0.0015 mg/kg to 0.0033 mg/kg), Nitrogen (N) in Percentage ranges from 2.3450% to 3.8550%; Phosphorus (P) ranges from 2.345 mg/kg to 3.607 mg/kg; Zinc (Zn) ranges from 2.215 mg/kg to 6.335 mg/kg. Lead (Pb) ranges from 0.00 mg/kg to 0.0015 mg/kg, potassium (K) ranges from 3.952 mg/kg to 6.213 mg/kg; Mercury and Arsenic nil. The study shows that Sweet Potato Peel (SDSPP) contains high Cadmium and potassium compare to other organic fertilizer produced. Sundried and Autoclaved Yam Peel (SDAYP) contains high percentage of Nitrogen (N), Heat Dried and Autoclaved Sweet Potato Peel (HDASPP) contains low Nitrogen, Sundried and Autoclaved Sweet Potato Peel (SDASPP) contains low phosphorus, Sundried Yam Peel (SDYP), Sundried and Autoclaved Yam Peels (SDAYP), Heat Dried Sweet Potato Peel HDSPP and Heat Dried Sweet Potato Peel (HDSPP) has zero trace of Lead (Pb) making it free of food intoxication from heavy metals, SDYP contains high phosphorus. These indicate that the samples will make quality organic fertilizer because it contains high Nitrogen, Phosphorus and potassium (NPK) which are essential elements required in plant structures.